2020
DOI: 10.1177/0047287520921245
|View full text |Cite
|
Sign up to set email alerts
|

Global Economic Policy Uncertainty and Tourism of Fragile Five Countries: Evidence from Time and Frequency Approaches

Abstract: The purpose of this study is to examine the relationship between global economic policy uncertainty (GEPU) and tourism activities in the Fragile Five (F5) countries, namely, Brazil, India, Indonesia, South Africa, and Turkey. By using wavelet transform context structures and the annual data during the period of 1997–2016. The finding shows that the relationship is generally positive but changes over time, displaying low- to high-frequency cycles. Moreover, the timing and frequency change when GEPU co-moves wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…1% rise in GEPU of the previous period leads to a fall in international tourism demand in Australia by 4.34% (AMG) method and 0.69% (CCEMG) method, respectively. Wu and Wu ( 2020 ) recommend that since tourism is sensitive to GEPU governments of the individual destination countries must pay attention to improving peace and security conventions.…”
Section: Resultsmentioning
confidence: 99%
“…1% rise in GEPU of the previous period leads to a fall in international tourism demand in Australia by 4.34% (AMG) method and 0.69% (CCEMG) method, respectively. Wu and Wu ( 2020 ) recommend that since tourism is sensitive to GEPU governments of the individual destination countries must pay attention to improving peace and security conventions.…”
Section: Resultsmentioning
confidence: 99%
“…Following the global financial crisis of 2008—the Great Recession—and the covid-19 pandemic, which decimated the country, the government and policymakers in South Africa have increasingly focused on uncertainty. For example, millions of South Africans lost their money, houses, and jobs as a result of the global financial crisis of 2008 (Wu and Wu 2021 ). The crisis wreaked havoc on the country's economy and created so much uncertainty that no one, even the government and policymakers, knew what the country's future contained.…”
Section: Introductionmentioning
confidence: 99%
“…Kisten ( 2020 ) discovered that EPU decreases industrial production and the actual effective exchange rate using a time-varying parameter (TVP) VAR approach for the period 1990–2015. Wu and Wu ( 2021 ), who studied the EPU-tourism nexus in South Africa, found a favourable link between EPU and tourist activities. Balcilar et al ( 2017 ) looked at the consequences of monetary policy uncertainty in South Africa and found that when uncertainty rises, interest rates, inflation, and production fall.…”
Section: Introductionmentioning
confidence: 99%
“…While a sizeable empirical literature has explored the negative impacts of economic policy uncertainty on international tourist arrivals (Shahzad et al, 2022; Tiwari et al, 2019; Wu & Wu, 2021), the findings continue to be ambiguous. Another strand in the literature has explored how the Geopolitical Index influences the tourism sector adversely (Balli et al, 2019; Lee, Olasehinde‐Williams, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%